Exploration of Decisions to Use Cash Management System Transactions for Millennial Customers - DHARMA, I Nyoman Setia; MARTINI, Ida Ayu Oka (PT Keberlanjutan Strategis Indonesia, 2024)
According to a new study, the number of electronic money users in Indonesia will reach 772 million by November 2023. The study states that electronic money is increasingly popular in Indonesia because of its convenience and practicality. The author says technology has brought significant changes to the financial sector. The data analysis technique used is qualitative analysis. Millennial customers think the BNI Direct Cash Management System is essential for business development. Payments have become easier with the BNI Direct Cash Management System, which is helpful for business owners and millennial customers. Applying the BNI Direct Cash Management System in payment systems in several research sectors can help with sound financial management as well as time and cost efficiency. Using the BNI Direct Cash Management System, this income optimization can occur because using the BNI Direct Cash Management System, both owners and the financial department of business actors can provide effective and efficient services with more comprehensive marketing access and obtain convenience in transactions, ease of transactions and speed of transactions, to increase people's purchasing power. This aligns with the expectations of people who want convenience in transactions, ease of transactions, and speed.